The Application of Seepage Flow Prediction in Nuer Dam Based on the Grey Self-Memory Model. (5th May 2022) - Wang, Ai-Feng; Yang, Xiu-Tao; Guo, Da-Hai
Abstract : The accurate time prediction of seepage pressure in the dam has essential significance for the safety of the dam body and the life and property of people. To predict the time sequence of seepage pressure, the grey self-memory model is introduced at first, and its calculative procedure is analyzed. Then, the engineering overview in the Nuer dam is narrated, and the prediction model of seepage pressure in the Nuer dam is established and analyzed based on the grey self-memory theory. Finally, the conclusions are drawn that relatively to GM (1, 1), the grey self-memory model has higher accuracy, and it not only can predict the time sequence of seepage pressure in the Nuer reservoir accurately but also provide a new method for the development trend of seepage flow in the hydraulic engineering in the future.